The influence of laser treatment on the properties of the surface of cylinder-piston group parts - Hlushkova Diana; Nikonov Oleg (Avtomobilʹnyj Transport (Harʹkov), 2020)
Various valuable materials and technological methods are used to increase the durability of the parts of the cylinder-piston group of internal com-bustion engines. The performance of internal com-bustion engines largely depends on the service life of the parts of the cylinder-piston group operating in conditions of friction, cyclic changes of power and temperature loads. Improving the durability of these parts is of great importance and is an urgent task. Goal. To calculate the influence of surface laser treatment on the structure and properties of high-strength cast iron used for the manufacture of piston rings is the goal of the work. Method. The treatment was performed with an ЛТ-1 laser continuous treat-ment. To increase the absorption capacity, the treat-ed surfaces of the samples were subject to blackening in various ways: oxidation and phosphating. The microstructure was studied in the initial state and after laser treatment. Microhardness was measured on a ПМТ-3 instrument. Phase analysis was per-formed by an X-ray. Results. The study has shown that the surface of cast iron melts over the entire area of contact with the beam at an irradiation rate of 6.4 mm / s, partially – at irradiation rates of 6.5; 7.6 mm / s. At a speed of 11 mm / s there is hardening of only the surface layer. The depth of the layer de-creases with increasing irradiation rate according to the parabolic law. At an irradiation rate of 5.4 mm / s, it is 1.3 mm, at 11 mm / s - 0.5 mm. The heteroge-neity is due to the short duration of the laser expo-sure. Studies of the microhardness of the melting zone also confirm the heterogeneity of its structure. The analysis of the structure and properties of the melted layers of cast iron showed that both during melting (reflowing) and hardening there is a signifi-cant strengthening of the surface layer. The above values of micro-hardness can be compared with the values of micro-hardness of not irradiated cast iron: Н = 2,2 2103… 3,6103 MPa. Novelty. Laser treatment promotes the formation on the friction surface of a heterogeneous structure that meets the requirements for antifriction materials. In this case, the laser treatment does not practically change the purity and configuration of the parts of the cylinder-piston group. Practical implementation. Industrial research shows that with laser treatment of piston rings the best is irradiation with surface hardening. In this case, violation of the mode, which causes partial melting of the surface, is not a reason to reject the parts. The work was implemented at the Malyshev Plant.